Non-price advertising and price competition: a theory, and evidence from the Brazilian beer market - Renato D. B. Gomes; Jo\~ao M. P. De Mello (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
By engendering horizontal differentiation, non-price advertising increases the incentives to accommodate on the price dimension. However, advertising also increases the size of the market and, consequently, the payoffs to price undercutting, which induces more aggressive price competition. We propose a theory in which advertising has a different effect on price competition according to the level of market maturity. In mature markets - where potential growth in low - only the price accommodation effect is present. In immature markets, both effects are present. Therefore, advertising is more procompetitive (less anti-competitive) in immature markets. Evidence from several Brazilian beer markets corroborates the theory.
Keywords: 330